If x and y are connected parametrically by the equation, without eliminating the parameter, find dy/dx x=sin^3t/(cos2t)^1/2, y=cos^3t/(cos2t)^1/2
Answers
Answered by
3
Given,
now, differentiate x with respect to t,
similarly![y =\frac{cos^3t}{\sqrt{cos2t}} y =\frac{cos^3t}{\sqrt{cos2t}}](https://tex.z-dn.net/?f=+y+%3D%5Cfrac%7Bcos%5E3t%7D%7B%5Csqrt%7Bcos2t%7D%7D)
now differentiate y with respect to t,
then ,we get ,
![\frac{dy}{dt}=\frac{-3cos2t.cos^2t.sint+cos^3t.sin2t}{cos2t\sqrt{cos2t}}-----(2) \frac{dy}{dt}=\frac{-3cos2t.cos^2t.sint+cos^3t.sin2t}{cos2t\sqrt{cos2t}}-----(2)](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdt%7D%3D%5Cfrac%7B-3cos2t.cos%5E2t.sint%2Bcos%5E3t.sin2t%7D%7Bcos2t%5Csqrt%7Bcos2t%7D%7D-----%282%29)
dividing equations (2) by (1),
![\frac{dy}{dx}=\frac{-3cos2t.cos^2t.sint+cos^3t.sin2t}{3sin^2t.cost.cos2t+sin^3t.sin2t}\\\\=\frac{cost.sint(-3cos2t.cost+cos^2.2cost)}{sint.cost(3sint.cos2t + sin^2t(2sint)}\\\\=\frac{-3(2cos^2t-1)cost + 2cos^3t}{3sint.(1-2sin^2t)+2sin^3t}\\\\=\frac{3cost-4cos^3t}{3sint - 4sin^3t}\\\\=\frac{-(4cos^3t-3cost)}{3sint-4sin^3t}\\\\=\frac{-cos3t}{sin3t}\\\\=-cot3t \frac{dy}{dx}=\frac{-3cos2t.cos^2t.sint+cos^3t.sin2t}{3sin^2t.cost.cos2t+sin^3t.sin2t}\\\\=\frac{cost.sint(-3cos2t.cost+cos^2.2cost)}{sint.cost(3sint.cos2t + sin^2t(2sint)}\\\\=\frac{-3(2cos^2t-1)cost + 2cos^3t}{3sint.(1-2sin^2t)+2sin^3t}\\\\=\frac{3cost-4cos^3t}{3sint - 4sin^3t}\\\\=\frac{-(4cos^3t-3cost)}{3sint-4sin^3t}\\\\=\frac{-cos3t}{sin3t}\\\\=-cot3t](https://tex.z-dn.net/?f=%5Cfrac%7Bdy%7D%7Bdx%7D%3D%5Cfrac%7B-3cos2t.cos%5E2t.sint%2Bcos%5E3t.sin2t%7D%7B3sin%5E2t.cost.cos2t%2Bsin%5E3t.sin2t%7D%5C%5C%5C%5C%3D%5Cfrac%7Bcost.sint%28-3cos2t.cost%2Bcos%5E2.2cost%29%7D%7Bsint.cost%283sint.cos2t+%2B+sin%5E2t%282sint%29%7D%5C%5C%5C%5C%3D%5Cfrac%7B-3%282cos%5E2t-1%29cost+%2B+2cos%5E3t%7D%7B3sint.%281-2sin%5E2t%29%2B2sin%5E3t%7D%5C%5C%5C%5C%3D%5Cfrac%7B3cost-4cos%5E3t%7D%7B3sint+-+4sin%5E3t%7D%5C%5C%5C%5C%3D%5Cfrac%7B-%284cos%5E3t-3cost%29%7D%7B3sint-4sin%5E3t%7D%5C%5C%5C%5C%3D%5Cfrac%7B-cos3t%7D%7Bsin3t%7D%5C%5C%5C%5C%3D-cot3t)
hence, dy/dx = -cos3t
now, differentiate x with respect to t,
similarly
now differentiate y with respect to t,
then ,we get ,
dividing equations (2) by (1),
hence, dy/dx = -cos3t
Similar questions
Math,
8 months ago
English,
8 months ago
Math,
1 year ago
Computer Science,
1 year ago
Math,
1 year ago